A Comparison of Nanotribological Characteristics between Synthetic Fiber and Human Hair - Yasmin, Rubiya; Kweon, Hyunkyu (International Journal of Integrated Engineering, 2020)
In this paper, an analysis of the nanotribological properties of human hair and nanocomposite artificial fibers is reported to discover a contiguous human hair replica. Investigation of a perfect artificial hair whose measurement properties should be nearby to the real hair is needed for and proposed. In practice, shallow experimental data exists for nanoscale correlation between heterogeneous subunits and their tribological properties. Synthetic fiber, Polyvinyl Chloride (PVC) fiber & Mod-Acrylic fiber are used as a model of composite artificial fibers. This paper designs and conducts the experimental range of nanotribological properties such as Surface roughness, Friction force, and Adhesive force. Therefore, associating with the closest tribological ranges, we have established a composite fiber which is healthy to human hair skin and suitable to wear without side effect or uncomfortable feelings.